Inter-organizational relationships and perceived innovation performance: The moderating role of social capital and mediating role of knowledge sharing - Aleema Shuja; Aleena Shuja (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study aims to analyze the role of inter-organizational relationship in boosting innovative performance of ICT enterprises through knowledge sharing supported by social capital. Gaining sustenance from Dynamic Capability View (DCV), the study investigates perceived enterprises' innovation performance as a result of inter-organizational relationships embedded with social ties and knowledge sharing among each other. Crosssectional data were collected from managerial level employees working in ICT enterprises in Pakistan. The study findings based on Process Hayes Macro regression analysis using SPSS stated that the ICT businesses in knowledge hub are collaborating to build strong social relationships while sharing practical experiences and support each other through abstract resources for achieving higher levels of innovative outcomes. Inter-organizational relationships have an affirmative impact on innovation performance, invariably, knowledge sharing mediates the correlation between both. The influence of interorganizational relationships on innovation performance through knowledge sharing is significant for firms with strong social capital. Consistently, social capital considerably moderates the relationships, as such organizations co-ordinate and work jointly with other organizations for driving service and product improvements. The research contributes by steers focus towards developing relationships among ICT enterprises, building ties based on faith and exchanging key information consistently to help and polish each other's innovation capabilities. Strong social ties among ICT enterprises will help acquire and capitalize on diverse knowledge to improve their innovation performance.
Keywords: 330; ICT enterprises; knowledge hub; inter-organizational relationships; social capital; knowledge sharing; enterprise's innovation performance; Pakistan